2011
DOI: 10.1016/j.jalgebra.2011.05.037
|View full text |Cite
|
Sign up to set email alerts
|

On some classes of integral domains defined by Krullʼs a.b. operations

Abstract: Let D be an integral domain with quotient field K. The boperation that associates to each nonzero D-submodule E of K, E b := {EV | V valuation overring of D}, is a semistar operation that plays an important role in many questions of ring theory (e.g., if I is a nonzero ideal in D, I b coincides with its integral closure). In a first part of the paper, we study the integral domains that are b-Noetherian (i.e., such that, for each nonzero ideal I of D, I b = J b for some a finitely generated ideal J of D). For i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…It is obvious that (iii) ⇒ (ii). For the reverse implication, it is enough to note that d T = b T is equivalent to T being Prüfer [21,Lemma 2].…”
Section: Spectral Semistar Operationsmentioning
confidence: 99%
“…It is obvious that (iii) ⇒ (ii). For the reverse implication, it is enough to note that d T = b T is equivalent to T being Prüfer [21,Lemma 2].…”
Section: Spectral Semistar Operationsmentioning
confidence: 99%
“…star operations of finite character. Fontana-Picozza [6] studied some classes of integral domains defined by the b-operation (in the more general setting of semistar operations). For example, they showed that if D is integrally closed, then This paper consists of four sections including introduction.…”
Section: Introductionmentioning
confidence: 99%